PERTUMBUHAN STUMP GMELINA (Gmelina Arborea Roxb.) PADA BERBAGAI PERBEDAAN LAMA WAKTU PENYIMPANAN - Misnawati, Misnawati; Yusran, Yusran; Rahmawati, Rahmawati (Universitas Tadulako, 2014)
Gmelina arborea Roxb, is a fast growing species that has been cultivated widely in forest plantation. This species can be used for various purposes, such as the stems can be used for furniture and construction and material for pulp and paper industry. This study aimed to determine the effect of various saving time on the growth of Gmelina (G.arborea Roxb.) stumps. The research was conducted from October through December 2013, at Taipa Java Nursery, Maesa, Palu, Central Sulawesi. The experiment was laid out in a Randomized Complete Design (RCD) with ten replications, Control that without saving time (P0), Stump saved 3 days (P1), Stump saved 6 days (P2), Stump saved 9 days (P3), Stump saved 12 days (P4). Observation Parameters consist of seedling height increment, steam diameter increment, leaf number, total fresh weight, total dry weight. The results of the study showed that there were significant differences between the treatments in all the parameters assessed. Treatment stump saved 9 days resulting the highest value in all the parameters and was significantly different from the other treatments in seedling height, stem diameter, leaf number and total fresh and dry weight, while the control treatment showed least performance in this study. Keywords : Saving Time, Growth, Stump, Gmelina arborea Roxb.